Modelling and assessing vocabulary knowledge - Daller, Helmut 1957-; Milton, James 1955-; Treffers-Daller, Jeanine 1959- (Cambridge applied linguistics, 2007)
Over the last 20 years vocabulary research has grown from a Cinderella subject to a position of some importance. Vocabulary is now considered integral to just about every aspect of language knowledge and is a lively and vital area of research and innovation. With this development have come standard and widely-used tests, such as vocabulary size and lexical richness measures, and commonly accepted metaphors, such as the mental lexicon as a web of words. Less widely known outside academic circles, however, is the extensive work on learners' lexis and the utility, reliability and validity of the tests we use to measure and investigate it. This volume brings together contributions from internationally-renowned researchers in this field to explain much of the background to study in this area. It introduces to a wider audience the concerns, the newest approaches and developments in the field of vocabulary research and testing